Placental transfer of inorganic ions and water - Stulc, J (Physiological reviews, 1997)
There are great interspecies differences in placental structure as well as in permeability properties of the placenta. In all species, however, the placenta behaves like a low-permeability barrier containing specific mechanisms of transcellular transport for minerals and other substrates for fetal growth and metabolism. The minerals that are contained in plasma in low concentrations and that are mainly intracellular or sequestered in bones (K+, Mg2+, Ca2+, phosphate) are transported to the fetus actively. The transfer of the main extracellular ions, Na+ and Cl-, exhibit great interspecies differences. In the sheep, the transfer rates of Na+ and Cl- to the fetus are consistent with passive transfer mechanisms. In the rat, Na+ is transported to the fetus actively and the transfer of Cl- is facilitated by a carrier and/or a channel. Transfer of minerals to the fetus is controlled by a variety of mechanisms ranging from very simple ones depending on intrinsic properties of the transport systems to complex mechanisms of hormonal control. Water is presumed to move across the placenta passively. The transfer may be facilitated by the 28-kDa water channel-forming integral protein (CHIP28), which is expressed in the trophoblast syncytium.
Keywords: antigeny krevních skupin; minerály; Rats; iontový transport; iontové kanály; Aquaporins; těhotenství; voda; chloridy; plod; placenta; Placenta; Water; krysa rodu Rattus; Ion Transport; Maternal-Fetal Exchange; Chlorides; ženské pohlaví; zvířata; Humans; akvaporiny; Pregnancy; Blood Group Antigens; permeabilita; Aquaporin 1; Permeability; sodík; akvaporin 1; Ion Channels; Fetus; Female; Minerals; Sodium; maternofetální výměna látek; lidé; Animals